2023
DOI: 10.1001/jamanetworkopen.2023.7888
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Clinical Outcomes and Cost-effectiveness Associated With Provision of Addiction Treatment in US Primary Care Clinics

Abstract: ImportanceUS primary care practitioners (PCPs) are the largest clinical workforce, but few provide addiction care. Primary care is a practical place to expand addiction services, including buprenorphine and harm reduction kits, yet the clinical outcomes and health care sector costs are unknown.ObjectiveTo estimate the long-term clinical outcomes, costs, and cost-effectiveness of integrated buprenorphine and harm reduction kits in primary care for people who inject opioids.Design, Setting, and ParticipantsIn th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…We describe the successful implementation of a QI pilot program integrating kits in our OBAT clinic. Our program extends prior work in hospital settings domestically in the US [ 30 ] and internationally [ 23 , 24 ] and serves as a real-world example addressing calls for harm reduction integration in outpatient care [ 7 , 12 , 26 , 27 ]. Our findings, albeit limited to one-month post-implementation, highlight a significant unmet need for kits even among patients with access to long-term addiction treatment.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We describe the successful implementation of a QI pilot program integrating kits in our OBAT clinic. Our program extends prior work in hospital settings domestically in the US [ 30 ] and internationally [ 23 , 24 ] and serves as a real-world example addressing calls for harm reduction integration in outpatient care [ 7 , 12 , 26 , 27 ]. Our findings, albeit limited to one-month post-implementation, highlight a significant unmet need for kits even among patients with access to long-term addiction treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous studies have demonstrated the significant positive impact of SSPs on patient and population-level outcomes [ 8 , 9 ]. SSPs, however, are not universally accessible in the US as a result of complex regional regulations [ 10 ] and so expanding these services to healthcare settings may increase access to harm reduction, be a cost-effective strategy [ 11 ], and improve clinical outcomes among PWUD [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have focused on community-based harm reduction, and early studies are examining harm reduction in primary care . Our study builds on these findings, with patients and staff viewing hospitalization as an opportunity to offer overdose prevention education and harm reduction supplies, particularly for communities missed by existing access points .…”
Section: Discussionmentioning
confidence: 99%
“…One recent modeling analysis suggested that the average primary care physician would incur approximately $13 000 in excess costs (both direct and indirect) over a 5-year period if they were to incorporate harm reduction into their practice. Notably, this was associated with a 33% decrease in mortality rate and decreased costs of hospitalization [ 41 ]. Given the required investment, we believe that mechanisms to compensate this work are needed both to encourage the development of such programs and promote their sustainability.…”
Section: Discussionmentioning
confidence: 99%